Reconception of history in the context of attention economy - S.A. Lieberman (Ученые записки Казанского университета: Серия Гуманитарные науки)
History functions and is defined depending on the historical context: in the modern era, it can be part of the national ideology; in Antiquity, it was perceived as a literary genre; in the Middle Ages, it was a religious worldview. In the post-capitalist era, theories about the “end of history” can also be explained as part of an ideologeme or a mythologeme. The paper aims to formulate the mechanisms of relations between the historical knowledge and the historical era. The functions of history in the contemporary world after the declared “end of history' were discussed. The concepts of attention economy and platform capitalism were considered as the basis for determining the specificity of contemporary society. The research focuses on the forms of re-actualization of the concept of history, which we can observe now, at the end of the second decade of the 21st century. How does the concept of history function? For what purpose is it reproduced after the “end of history” and the “death of the social” proclaimed in the late 20th century? Can such re-actualization be considered a “Renaissance” of the social? These are the main questions covered by this paper.